Pedoman Tata Laksana Fibrilasi Atrium Perhimpunan Dokter Spesialis Kardiovaskular Indonesia 2014 - Yoga Yuniadi; Dicky A Hanafy; Sunu B Rahardjo; Alexander E Tondas; Erika Maharani; Dony Y Hermanto; Muhammad Munawar (Jurnal Kardiologi Indonesia, 2014)
Atrial fibrillation is the most frequent arrhythmia in clinical practice and causing huge health problem. Therefore, a national guidelines in management of AF that comprise of pathomechanism, clasifications, anticoagulants management for stroke prevention, rate and rhythm control is developed to ensure patients get best therapeutic option. The guidelines is developed in line with variable health care level in Indonesia from primary up to tertiary care.